Kajian Pemanfaatan Puskesmas Di Kecamatan Pekalongan Barat Kota Pekalongan Tahun 2015 - Nugroho, Tedi Septiawan, Drs. Priyono, M.Si, Dra. Umrotun, M.Si (2016)
The utilization of PHC is to use all the facilities and health services provided by the public health center for the benefit of medical consultation and treatment of both physical and spiritual. In 2015, there were differences in the number of visitors at each health center in the district of West Pekalongan. Two of them have reached the standard of a minimum of 30,000 inhabitants per year of service and the rest have not reached the standard of a minimum of 30,000 inhabitants per year. Thus it is possible there is a cause of the difference in the number of visitors, both in socio-economic factors and environmental factors around the health center. Quality of care, socioeconomic factors and environmental factors surrounding community health centers may be the cause of differences in the number of visitors, so in this study aims to determine how much the level of service quality in the eyes of society and socio-economic factors that influence the level of public visits to the health center. The method used in this study was the scoring method and correlation method. The scoring method used to compare the quality of health center services in the District of West Pekalongan and utilization rate of PHC. Correlation method is used to determine the relationship or closeness between the socio-economic conditions of society and the environment community health centers with traffic levels take advantage of the health center. Quality of care at health centers in the district of West Pekalongan have the same quality is very good service quality, it appears that the resulting score of more than 9.2. PHC utilization factors exist that do not have a relationship and have a weak relationship to the respondent visits to the health center. The utilization rate of health centers in the district of West Pekalongan there are two levels in the form of high-level pamanfaatan health center and health center utilization rate was.